How Can Participatory Methods Centre Teachers Within Education Policy? - Koomar, Saalim (EdTech Hub, 2024)
This Learning Brief is part of the EdTech Hub Learning Brief Series, providing practical resources for people working to improve the use of technology in education. In this brief, we look at the potential for participatory methods to bring teachers closer to the decision-making table. Insights from those closest to the work shed light on the daily contextual realities that can determine the mechanisms for optimal success or failure of a programme. However, these voices are often neglected in the design, implementation, and evaluation of interventions. We examine why and how teachers can have a voice and a space to share their wisdom to inform and improve education policy. We draw on EdTech Hub's work across various low- and middle-income contexts to offer practical insights when using or planning to use participatory methods. We share details of some of the most significant findings and engaging lessons EdTech Hub has learnt about the methods used and how they have contributed to ensuring teachers’ voices are heard at the policymaking level. We also explore areas that require further research, noting five issues that we at EdTech Hub are still grappling with in our own work, and include lists of resources relevant to participatory methods for centring teachers in education policy. Keywords: teacher; participatory methods; action research; implementation research; teacher professional development; education policy An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence; _r:AddedByZotZen

Investigating the Activity Levels of School Quality Assurance Officers in Sierra Leone - Beoku-Betts, Iman; Leh Wi Lan (EdTech Hub, 2023)
Since the launch of the Free Quality School Education (FQSE) Programme in 2018, the Sierra Leone Ministry of Basic and Senior Secondary Education (MBSSE) has prioritised the use of data for decision-making across several education reform programmes. Part of this vision has been to build systems to measure school quality through School Quality Assurance Officers (SQAOs) using data collection and feedback. This system includes using tools for teacher management, lesson observations, school improvement, and attendance monitoring. This report presents findings from qualitative research conducted in three districts in Sierra Leone. The aim is to provide the MBSSE and other partners with insights to understand the variation in and what is needed to maximise SQAO activity levels, increase principal engagement with digital tools, and support and promote quality visits to schools. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Testing EdTech Interventions in Bandarban: Key Findings from the EdTech Hub Sandbox - Tanweer, Rabia; Plaut, Daniel; Datta, Rupa; Nashtaran, Trishia; Rahman, Asad; Ahmed, Shakil; Fazly, BMRabbi; Hoque, Rashedul; Moon, NurunNahar; Afroze, Sadia (EdTech Hub, 2023)
The Covid-19 pandemic has catalysed the need for technology-enhanced education globally. This is no different in Bangladesh, where the Education Section of the UNICEF Bangladesh Country Office is seeking a better understanding of the role and potential of EdTech to improve numeracy skills among the most marginalised learners. In efforts to do this, UNICEF Bangladesh partnered with EdTech Hub to in which EdTech interventions contribute the most to numeracy learning for marginalised learners in Bangladesh. This was explored through a sandbox in Bandarban, a remote region in South-Eastern Bangladesh. This report synthesises the evidence generated from this EdTech Hub sandbox. While further research is needed, its findings suggest that multimedia classrooms, which were found to be present and functioning in most schools in the region, are a promising intervention. Their effectiveness and implementation are worthwhile avenues for further research. Keywords: Bangladesh, Low connectivity/electricity, rural, marginalised learners, blended learning, tablets An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Sierra Leone Series: Plan International and the importance of community support for distance teacher professional development programmes - McBurnie, Chris; Saidu, Arthur; Rincon Casado, Eusebio; Shergill, Maggie (EdTech Hub, 2021)
Keywords: _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:analysis:nopdf; _r:AddedByZotZen

Sierra Leone series: Plan International and the importance of community support for distance teacher professional development programmes - Saidu, Arthur; Casado, Eusebio Rincon; Shergill, Maggie; McBurnie, Chris (EdTech Hub, 2021)
Over the past few months, the EdTech Hub team has analysed and mapped the EdTech research landscape in Sierra Leone. In doing so, we have met a number of individuals and organisations that are exploring if and how technology can support the country’s education sector.  In week four, we met with Arthur Saidu, Eusebio Rincon Casado and Maggie Shergill from…
Keywords: _DOILIVE; _EdTechHub_Output; ___working_potential_duplicate; _zenodoETH

Minoritised Languages, Education, and Technology: Current practices and future directions in low- and middle-income countries - Zhao, Annette; Mitchell, Joel; Gasanabandi, Gentille; Ullah, Noor; Barnes, Katrina; Koomar, Saalim (EdTech Hub, 2024)
This article explores the current status and future directions of mother-tongue-based multilingual education (MTB MLE) and the use of technology in low- and middle-income countries (LMICs), focusing on the use of minoritised mother tongues. An initial literature review of available academic sources in multiple languages reveals a lack of evidence on the use of technology in MTB MLE across different countries, especially multilingual contexts with greater linguistic diversity. To understand the issue in greater detail and to offer recommendations informed by current practice, interviews and a collaborative workshop with four organisations with relevant educational technology (EdTech) initiatives were conducted. The analysis covers facilitating and limiting factors these organisations have encountered, and the potential positive impact on learners and society generally. We conclude by identifying practical, policy, and research priorities for multilingual education and educational technology in general.
Keywords: _r:AddedByZotZen